Analisis Minat Nasabah Untuk Melakukan Pembiayaan Pada Bank BSI KC Kualasimpang : (Studi Kasus Pada Bank Syariah Indonesia KC Kualasimpang) - Dwi Restu Tanjung; Ahmad Perdana Indra (FEB Universitas Maritim Semarang, 2023)
Banks that carry out their business activities based on sharia principles, or principles of Islamic law, are called sharia banks. As time goes by, Islamic banks are starting to have more Muslim customers. Bank BSI Kc Kualasimpang, for example, has active Muslim customers. Muslims are known to have great interest in Islamic sharia banking. BSI Bank Kc. Kualasimpang operates based on sharia principles and does not provide payment services. Because the data was obtained from direct observations at BSI Kc Kualasimpang, this is a type of field research. This study uses a qualitative methodology. Primary and secondary data were used in this research. Primary data consists of a description of the factors that influence non-Muslim customers. Secondary data consists of books related to the research topic. The author found two components: internal and external factors. The research results show that of the internal and external factors studied, the dominant external factors influencing non-Muslim customers' interest in BSI Kc Kualasimpang are promotion, service, location and social level. Work and motivation are internal factors. The more promotions and services offered by banks to non-Muslim customers, the more likely they will join an Islamic bank.